PENENTUAN POTENSI LAHAN UNTUK TANAMAN KEDELAI DAN CENGKIH DARI DATA LANDSAT TM DAN IKLIM DI KABUPATEN BANYUWANGI DENGAN SISTEM INFORMASI GEOGRAFIS - Ety Parwati; Indah Prasasti; Iskandar Effendy (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
Clove and soybean are plantations that have high enough economic pontetial. Both of these commodities need suitable land climate condition to grow in optimum. The process of Remote Sensing and climate data with Geographic Information System can determine a suitable land for clove and soybean plantations. Land potential evaluation uses Land Use data that is extracted from Landsat-TM data. The land suitability level is then determined based on climate parameter (rainfall and draught period) and land physical properties for sorbean and clove in Banyuwangi Regency.